Kajian Pustaka Metode Optimasi Respons Surface Methods dan Thin Layer Equation pada Produk Pengeringan Rempah Rimpang (Jahe, Kunyit, Temulawak) - Maria Krisna Evania; Fransiska (Program Studi Teknologi Hasil Pertanian, 2024)
Ginger, turmeric, and curcuma are rhizome spices that have the highest production value in Indonesia. Fresh products from rhizomes have high water content and are often damaged by microorganisms. For this reason, proper and efficient processing is needed so that the quality of the rhizome spices is maintained and under the standards set by the Indonesian National Standards. One of the appropriate processing methods for rhizome spices is the drying method. Drying is the oldest technique for food preservation and is an indispensable process in the food industry. The drying process aims to reduce water content and activity to safe limits that can extend shelf life, minimize packaging demands, and reduce weight during distribution. Various conventional and modern drying techniques have been applied to spices, namely solar drying, oven drying, and microwave drying. To obtain final drying results in good quality and high drying efficiency, it is necessary to optimize the drying method process conditions, including mathematical modelling using the RSM (Response Surface Method) method and the Thin Layer Drying Equation. From the optimum conditions for each drying method, a regression analysis was then carried out on several drying quality parameters for ginger, turmeric, and ginger. The higher the value of the regression coefficient (R2) and the closer it is to 1 in the mathematical modelling obtained, then this mathematical modelling is the best.